In Silico Design Gene Encoding CYP71AV1 for Expression in Escherichia coli - Ulfa, Evi Umayah (Universitas Airlangga, 2022)
Cytochrome P450 monooxygenase (CYP71AV1) is a crucial enzyme in the artemisinin biosynthesis pathway. This enzyme oxidized Amorpha 4,11 diene to produce artemisinic acid. This study aimed to in silico design high-level expression of CYP71AV1 in the E.coli system. In silico techniques are highly suitable for designing protein recombinant production before entering the laboratory. The amino acid sequence of CYP71AV1 was back-translated to the DNA sequence and adapt to E.coli codon usage by using Gene Designer. The DNA sequence of optimized CYP71AV1 was analyzed using Rare Codon Analysis to assess the expression efficiency in E.coli. The protein solubility prediction was determined using the SoDoPe tool. The optimized CYP71AV1 was determined to have a CAI 0.81, a GC content of 53.08 %, CFD with low frequency, and no negative cis or repeat elements. The result of the probability of solubility of CYP71AV1 was 0.6207 when expressed in E.coli. The MBP fusion partner can be used to increase the solubility of CYP71AV1. The in silico results showed the possibility of high-level protein expression of optimized CYP71AV1 in the E.coli system.